Obtaining and Characterization of New Materials, Volume II - Sandu, Andrei Victor (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
A collection of articles published under the guidance of Assoc. Prof. Ph.D. Andrei Victor SANDU in the Special Issue "Obtaining and Characterization of New Materials, Volume II". The published articles under this Special Issue represent an excellent collection of research and review articles with cutting-edge results that promote sustainable development in the field of material engineering.